Promoting Photovoice for Teachers’ Self-Reflection on Multimodal Literacy - Nur Arifah Drajati; Ngadiso Ngadiso; Hasan Zainnuri (Institut Agama Islam Negeri Imam Bonjol Padang, 2019)
Self-reflection is a concept of learning from experience that dominates teacher educator around the world. It is true that self-reflective is not a natural process since it needs critical thought, self-direction, and problem-solving with personal knowledge and self-awareness. The major premise of the study is that although teachers are repeatedly encouraged to reflect on their teaching and learning, they are unable to do so successfully. Photovoice is a valuable tool to engage teachers in reflecting their own lives outside the school voice their perspectives and share with other teachers, students, and policymakers. Thus, the purpose of this study is to report on action research that investigated photovoice in emerging teachers’ self-reflective on multimodal literacy. To examine this issue, a qualitative study with an action research design was conducted with five junior high school teachers as participants. The data collected through photovoice and analyzed by using SHoWeD Analysis. SHoWeD analysis is the acronym for a series of questions: (1) what do you see here; (2) what is happening; (3) how does this relate to our lives; (4) why are things this way; (5) how could this image educate people. In general, the study indicates that the use of photovoice for self-reflective on multimodal literacy gives positive impacts on the context of teacher professional development